Dr Jekyll and Mr Hyde Level 3 - Stevenson, Robert Louis; Hopkins, Andy; Potter, Jocelyn (England Pearson Education Ltd, 2008)
This book explains why the scary Mr Hyde is friends with the nice Dr Jekyll? Who is the evil little man? And why does he seem to have power over the doctor? After a terrible murder, everyone is looking for Mr Hyde. But he has disappeared. Or has he?
Keywords: Tham khảo